Role of Leadership in Adoption of Blockchain Technology in Small and Medium Enterprises in Saudi Arabia - Alshareef, Nasser; Tunio, Muhammad Nawaz (Frontiers in Psychology, 2022)
This research aims to determine the role of the leadership and potential benefits that blockchain adoption may bring to SME financing in the Kingdom, as well as the foreseeable challenges that may hinder small businesses from benefiting from the adoption of blockchain. It is interesting aspect to see how leadership manages to adopt new changes amid several challenges and threats. This article also outlines policy and regulatory trends that SMEs can save operating costs and improve efficiency, thereby increasing transparency and easier access to funds. Digital technology and creative business models have the potential to help narrow the financing gap for SMEs. E-commerce and the sharing economy provide SMEs with more market access and new business models, as well as the data-driven business prospects generated through data sharing under the framework of open banking. This study provides recommendation that there is a dire need to pay attention on the complete mechanism of the SME’s in order to support them as well as promote them to show their distinction in the contribution of social and economic development. This study provides implications for the financial institutions, government agencies and society to come forward equally for the common interest.